2005
DOI: 10.1007/s10549-005-9063-1
|View full text |Cite
|
Sign up to set email alerts
|

Pre-diagnosis physical activity and mammographic density in breast cancer survivors

Abstract: Purpose-To investigate the association between physical activity (PA) and mammographic density in the year before diagnosis in a population-based sample of 474 women diagnosed with stage 0-IIIA breast cancer and enrolled in the Health, Eating, Activity, and Lifestyle Study.Methods-We collected information on PA during an interview administered at a baseline visit scheduled within the first year after diagnosis. Participants recalled the type, duration, and frequency of different PAs for the year prior to their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
38
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 23 publications
6
38
0
Order By: Relevance
“…13 However in agreement with our results, a statistical significant decline in MBD area and percent density with increasing level of prediagnostic recreational PA in obese (BMI 30 kg/m 2 ) postmenopausal women emerged. The collection of information on PA was accurate, extended to several activities and MET hours/week were calculated.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…13 However in agreement with our results, a statistical significant decline in MBD area and percent density with increasing level of prediagnostic recreational PA in obese (BMI 30 kg/m 2 ) postmenopausal women emerged. The collection of information on PA was accurate, extended to several activities and MET hours/week were calculated.…”
Section: Discussionsupporting
confidence: 92%
“…The methods to assess PA and the components of PA investigated varied widely. Some studies suggested an inverse association between PA and high MBD 12,13 or a positive association with hours of inactivity, 14 while others reported no association. 10,[15][16][17][18] We have carried out a study on 2,001 healthy women to prospectively investigate the influence of baseline individual characteristics related to dietary and life style habits on MBD, as assessed by mammographic examinations (MEs) performed 5 years after the enrolment in the cohort.…”
mentioning
confidence: 99%
“…Also similar to our findings, Siozon et al showed that associations between physical activity and breast density were no longer significant after adjusting for BMI (26). Conversely, two studies conducted in distinct populations have reported results consistent with an inverse association between physical activity and breast density (27)(28)(29). In a multi-ethnic study of 474 U.S. women, Irwin et al reported that higher levels of sports/recreational physical activity were associated with lower dense breast area and percent density among obese postmenopausal women [mean (SD) MET-h/wk = 7.8 (12.6)] yet were associated with an increase in percent density among nonobese premenopausal women [mean (SD) MET-h/wk = 19.4 (21.8); ref .…”
Section: Discussionsupporting
confidence: 90%
“…Significant positive associations between hours of mild exercise per week and both dense area and percent density were observed among well controls in multivariable models; however, given the number of statistical comparisons, lack of other significant associations, and the inconsistency of this finding with all prior studies of physical activity and mammographic density (19,(23)(24)(25)(26)(27)(28)(29), these findings are likely due to chance. Physical activity was not significantly associated with dense breast area before or after adjustment for BMI.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation